2007
DOI: 10.1080/15216540701510581
|View full text |Cite
|
Sign up to set email alerts
|

Let's stick together: The role of the Fras1 and Frem proteins in epidermal adhesion

Abstract: SummaryThe Fras1 and Frem extracellular matrix proteins play critical roles in epithelial-mesenchymal interaction during embryonic development. Loss of function in humans results in a recessive embryonic blistering disorder called Fraser syndrome. Inactivation of these proteins, or the proteins with which they interact (e.g., Grip1) has also been shown to underlie members of the 'bleb' family of classic mouse mutants which provide a valuable model of Fraser syndrome. Recent studies supporting direct interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 36 publications
2
57
0
5
Order By: Relevance
“…Similar expression of other ECM components at this stage have previously been noted in zebrafish (Yan et al, 1995;Higashijima et al, 1997) and morphological studies of the hypochord have shown that it develops ultrastructural characteristics of an epithelia, including a well-defined basal lamina (Eriksson and Lofberg, 2000). Mammalian studies suggest that many Fras/Frem interactions also take place in the context of a basement membrane (reviewed in Short et al, 2007). We noted persistent expression of frem3 in this structure until approximately 27 hpf, the point at which expression in the myotome is also beginning to decline.…”
Section: Hypochord Expression Of Frem3mentioning
confidence: 76%
See 1 more Smart Citation
“…Similar expression of other ECM components at this stage have previously been noted in zebrafish (Yan et al, 1995;Higashijima et al, 1997) and morphological studies of the hypochord have shown that it develops ultrastructural characteristics of an epithelia, including a well-defined basal lamina (Eriksson and Lofberg, 2000). Mammalian studies suggest that many Fras/Frem interactions also take place in the context of a basement membrane (reviewed in Short et al, 2007). We noted persistent expression of frem3 in this structure until approximately 27 hpf, the point at which expression in the myotome is also beginning to decline.…”
Section: Hypochord Expression Of Frem3mentioning
confidence: 76%
“…In addition to their generalized expression in the developing epidermis/dermis they are also transcribed at sites in which differentiating and proliferative epidermal components are involved in active signalling with underlying mesenchyme. These include the developing limb, hair follicle, eyelid, lung, mammary gland, and kidney (Short et al, 2007). Frem2 is also expressed in a complex pattern in the developing musculature, branchial arches, and central nervous system (Jadeja et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Well-studied adhesion systems, such as focal adhesions, are associated with numerous proteins (Kuo et al, 2011). As Hmcn1 was identified as a regulator of Fraser syndrome, a disease that is attributed in part to transient basement membrane disruptions and blistering below the basement membrane of the epidermis (Short et al, 2007;Smyth and Scambler, 2005), other genes associated with Fraser syndrome might also encode B-LINK components. In addition, further studies in C. elegans using forward genetic analysis will likely reveal additional B-LINK proteins.…”
Section: Basement Membrane Linkages Connect Tissuesmentioning
confidence: 99%
“…Fraser syndrome is characterized by cryptophthalmos, cutaneous syndactyly, malformations of the larynx and genitourinary tract, craniofacial dysmorphism, orofacial clefting, mental retardation, and musculoskeletal anomalies. Mutations in the extracellular matrix proteins Fras1 and Frem are associated with this syndrome [129]. Hand-foot-uterus syndrome is characterized by abnormalities of the hand, foot, urinary tract, and reproductive tract.…”
Section: Multi-class Diseasesmentioning
confidence: 99%